Hydrocarbon fractions from the thermal cracking of polyolefin wastes - synthesis, purification and applications - Walendziewski, J. (Polimery, 2010)
The cracking of polyolefin waste mixtures performed in industrial and laboratory scale installations under conditions of varying temperature, pressure and reaction time has been carried out. The obtained products were separated into gasoline and oil fractions and then hydrorefined. The results confirm that the application of the easily available calcium hydroxide significantly reduces the amount of chlorine in the liquid hydrocarbon fractions (Table 1) and that hydrorefining is an effective method for the purification of petrol and oil fractions (Tables 2 and 3). Depending on their composition and properties, the products obtained according to the presented method of cracking of polyolefin wastes can be applied as fuel components, raw materials for the production of solid and oil paraffin (Table 4-7).